Jah Hills - Slasha, Unathi (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
Jah Hills is alone in Kwaf Indoda bush, waiting for elders to come, burn ibhuma and deliver him home. Two weeks before he departs from his initiation period, he is seduced by igqwirha. When he fails to satisfy her appetite, he gets 'abducted and turned into isithunzela. One night, he narrowly escapes and finds his way back. But the experience at home is gruesome; they drive him away and want his death. My novel is fast paced, accumulating speed as it proceeds. It is formally experimental, drawing on forms that have gone before and trying to usher in a new manner of writing and looking at the world. It is told through the eyes of isithunzela that Jah Hills has become. It makes use of Nguni folklore, reimagined and subverted so it fits the character's unearthly vision. Certain characters and moments from Nguni folktales are borrowed and appear throughout the text. Stylistically I draw extensively from the work of Sony Lab'ou Tansi, Taban Lo Liyong, Dambudzo Marechera, D.O. Fagunwa and Amos Tutuola.
Keywords: Uncatalogued